A novel pathogenic variant in the corneodesmosin gene causing generalized inflammatory peeling skin syndrome with marked eosinophilia and trichorrhexis invaginata. Issue 2 (17th February 2022) - Gordon, Helen; Yap, Patrick; Hsiao, Kuang‐Chih; Watson, Michael; Purvis, Diana
Abstract: Generalized inflammatory peeling skin syndrome (PSS) is a rare autosomal recessive genodermatosis caused by loss‐of‐function disease‐causing variants of the corneodesmosin gene ( CDSN ), resulting in excessive shedding of the superficial layers of the epidermis. We describe a case of generalized inflammatory PSS in an infant, presenting at day two of life with ichthyosiform erythroderma and superficial peeling of the skin. Hair microscopy showed trichorrhexis invaginata. Normal amounts of skin LEKT1, a product of SPINK5 on immunohistochemical staining excluded a diagnosis of Netherton syndrome. Genetic analysis revealed a homozygous novel complete CDSN deletion, estimated 4.6 kb in size, supporting the diagnosis of generalized inflammatory PSS.